2007
DOI: 10.1007/s10681-006-9278-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the two cultivated rice species (O. sativa & O. glaberrima) in Maritime Guinea. Evidence for interspecific recombination

Abstract: In Maritime Guinea, the interpenetration of upland, lowland and mangrove rice growing ecosystems has found expression in the cohabitation of the two rice cultivated species. Recent changes in cropping practices may lead to the replacement of local varieties by modern high-yielding varieties. In the framework build-up of a strategy for the preservation of local varieties, we analysed the extent, the organisation and the specificities of the rice genetic diversity. One hundred seventy accessions collected in far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…The lack of introgression of the donor parent genome in some lowland NERICA lines could explain some phenotypical differences observed during vegetative and reproductive stages of these lowland NERICAs. Indeed, the genome of the O. glaberrima parent can be partially introgressed on progenies when the crosses are carried out with an O. sativa variety (Barry et al, 2007). Also intensive selection occurred during the selfing of the BC 2, BC 3 and BC 4 generations according to the number of the traits concerned.…”
Section: Lowland Nerica Structuringmentioning
confidence: 99%
“…The lack of introgression of the donor parent genome in some lowland NERICA lines could explain some phenotypical differences observed during vegetative and reproductive stages of these lowland NERICAs. Indeed, the genome of the O. glaberrima parent can be partially introgressed on progenies when the crosses are carried out with an O. sativa variety (Barry et al, 2007). Also intensive selection occurred during the selfing of the BC 2, BC 3 and BC 4 generations according to the number of the traits concerned.…”
Section: Lowland Nerica Structuringmentioning
confidence: 99%
“…Asian rice (Oryza sativa L.), comprises two main sub -species which are indica (adapted to floating tropical and subtropical regions or lowland and irrigated agricultural systems) and japonica (adapted to tropical highlands) (Tendro Radanielina et al, 2013). Several collections of these species (Oryza sativa L., and Oryza glaberrima Steud) exist throughout the world (Barry et al, 2007) and mostly at the genebanks of IRD in France, The…”
Section: Introductionmentioning
confidence: 99%
“…Local varieties are valuable as they possess a huge treasure of genetic material for development and improvement programs. Several researchers reported the use of agromorphological markers in the characterization and study of rice (Oryza sativa L.) germplasm diversity in China (Yawen et al, 2003), India (Roy et al, 2013), Vietnam (Nguyen et al, 2009), Nepal (Mahendra et al, 2013) and even in Africa (Semon et al, 2005;Barry et al, 2007;Nuijten et al, 2009;Sow et al, 2013). In Benin and in our knowledge, no genetic diversity study on rice is reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, landraces are adapted to local agro-environmental conditions which contributes to yield stability and hence, they continue playing an important role in traditional and subsistence farming (Camacho-Villa et al, 2005). However, extensive efforts to improve rice productivity have led to large-scale cultivation of highyielding genetically uniform varieties, the replacement of local cultivars and the concomitant decrease in rice genetic resources that created a widespread concern to promote conservation of traditional cultivars/landraces (Kohli et al, 2004;Camacho-Villa et al, 2005;Barry et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite markers has been used to study interspecific relationships between Oryza sativa and either wild (O. rufipogon and O. nivara) or cultivated (O. glaberrima) species (Ni et al, 2002;Barry et al, 2007). Ni et al (2002) also determined the pattern of diversity in indica and japonica rice subspecies and, within the japonica group, in both temperate japonica and tropical japonica types.…”
Section: Introductionmentioning
confidence: 99%